CSA-CIS MSD workshop report focusing on aquaculture - Kakwasha, Keagan; Lundeba, Mary; Kanyembo, Henry; Kagabo, Desire; Mudege, Netsayi N. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
WorldFish, in collaboration with the International Water Management Institute (IWMI), hosted a multistakeholder dialogue (MSD) platform at a workshop held in Mansa, Luapula Province, on April 28, 2022. A total of 78 participants, 31% of whom were women, attended the workshop. The Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA Zambia) project launched an MSD in February 2022 to share ideas on how to scale climate-smart aquaculture (CSA) and climate information services (CIS). The workshop in Mansa was one in a series of meetings planned for the AICCRA Zambia CSA-CIS MSD platform. This particular MSD workshop focused on aquaculture, especially issues related to (i) financing for smallholder farmers and small- and medium-scale enterprises (SMEs) in the face of climate change, (ii) benchmarking and credit worthiness of a smallholder fish farmers, and (iii) sharing practical experiences from integrated fish farms, the Aquaculture Development Association of Zambia (ADAZ) and banks. In addition, participants also made a field visit to an integrated fish farm in Samfya District, Luapula Province.